Career Guidance in Preparing Students with Disabilities for Get in to the Worke in Preparing Students with Disabilities for Get in to the Work - Liah Siti Syarifah (STKIP Melawi, 2021)
Abstract: This research aims to describe career guidance for students with disabilities in special schools (SLB). This research uses a qualitative approach with descriptive methods. The research subjects were the Principals and Teachers at SLB Negeri 1 Subang, SLB SLB Maliwis, SLB Negeri Cicendo, SLB Sukapura, SLB Negeri Handayani and SLB PGRI and the object of research was the implementation of career guidance for deaf and mentally retarded students. By using purposive sampling technique, the sample taken is the principal and teachers of skills subjects and/ or teachers accompanying apprentices. The data collection techniques in this research were carried out by observation, interviews and documentation study. And the data analysis technique used in this research was an interactive data analysis model. Based on the research, it was found that career guidance for deaf students was carried out with an individualized instructional approach and career guidance for students with mild mental retardation was carried out using the drill method. Based on the research results, career guidance services provided to students with disabilities are carried out using different methods and subject matter. Keywords: Career Guidance, Disabilities, Students Work